Design of inerter-based multi-actuator systems for vibration control of adjacent structures - Palacios-Quiñonero, F.; Rubió-Massegú, J.; Rossell, J.M.; Karimi, H.R. (Journal of the Franklin Institute, 2019)
Distributed multi-actuator systems can provide effective solutions for mitigating the vibrational response of large structures. In this paper, we present a computational strategy to design inerter-based multi-actuation systems for the seismic protection of adjacent structures. The proposed approach allows considering both interstory and interbuilding Tuned Mass-Inerter Damper (TMID) actuators, and aims at simultaneously reducing the vibrational response of the individual buildings and avoiding the interbuilding impacts. The tuning procedure is based on an H∞ cost-function and uses a constrained global-optimization solver to compute parameter configurations with high-performance characteristics. To illustrate the main features of this work, two different Tuned Inerter Damper (TID) multi-actuator schemes are considered for the seismic protection of a particular multi-story two-building system. A multi-actuator Tuned Mass Damper (TMD) system is also designed and is taken as a reference in the performance assessment. The obtained results demonstrate the flexibility and effectiveness of the proposed design methodology, and clearly show the superior performance and robustness of the TID actuation systems.